Helminth fauna of Astyanax fasciatus Cuvier, 1819, in two distinct sites of the Taquari River, São Paulo State, Brazil - Acosta, Aline Angelina [UNESP] (2015)
This study assessed the helminth fauna of Astyanax fasciatus in two distinct sites of the Taquari River, São Paulo State, with 30 individuals sampled in a lotic site and 30 in a lentic site, recording the monogeneans: Cacatuocotyle paranaensis, Characithecium costaricensis, Diaphorocleidus kabatai, Jainus sp., Notozothecium sp. and Gyrodactylus sp., the digenean Antorchis lintoni and no-identified metacercariae; the nematode Procamallanus (Spirocamallanus) inopinatus and no-identified larvae. The mean abundances of total monogeneans (U = 1053; p = 0.042) and C. costaricensis (U = 1107; p = 0.005) were higher in the lotic site. This difference may be due to the higher density of the host population in the lotic site, and the water transparence in lentic environments that prevents A. fasciatus to form shoals, precluding the exchange of parasites with direct cycle within a host population. This study is the first report of the helminth fauna of A. fasciatus in the Taquari River, with ten taxa recorded, and reports A. fasciatus as a new host for Notozothecium sp. and C. paranaensis.